Zondervan handbook to the Bible - Alexander, David, 1937-2002.; Alexander, Pat, 1937- (Grand Rapids, MI : Zondervan, 2009)
Study guide for the Bible.
Published by special arrangement with Lion Publishing.
Includes index.
Keywords: Bible -- Handbooks, manuals, etc